Nearly One in Three Lactating Mothers Is Suffering from Inadequate Dietary Diversity in Amhara Region, Northwest Ethiopia - Netsanet Fentahun; Elisabeth Alemu (Journal of Nutrition and Metabolism)
Background. In developing countries, dietary diversity is a challenge for rural communities especially pregnancy and lactation. Malnourished mothers are unable to combat disease and feed adequate nutrients to their children, and this will in turn affect the socioeconomic development of the country. To date, there is paucity of evidence regarding predictors of dietary diversity among lactating mothers in developing countries. The main objective of this study was to determine the extent and predictors of dietary diversity among lactating mothers in Lay Gayint District, Amhara Region, Ethiopia. Methods. A community-based cross-sectional study design was employed on 416 systematically selected lactating mothers from March 1–30, 2018. The data were collected using pretested interviews. Data were entered and analyzed using SPSS version 21 software. Bivariable and multivariable logistic regression models were used to determine the predictors of dietary diversity. Odds ratio with 95% confidence interval and p ≤ 0.05 were used to test the association. Result. A total of 268 (65.7%) lactating mothers had inadequate dietary diversity. Adequate dietary diversity was significantly associated with mobile phone usage (OR: 2.3; 95% CI: 1.15–4.55); practice of home gardening (OR: 4.1; 95% CI: 1.71–9.87); pulses production (OR: 4.8; 95% CI: 2.50–9.32); delivery in health center (OR: 4.7; 95% CI: 1.80–12.25); food secured household (OR: 2.4; 95% CI: 1.25–4.62); three meals per day within the previous seven days (OR: 11.12; 95% CI: 2.74–45.24); and practice of income generating activity (OR: 4.00; 95% CI: 2–8.33). Conclusion. Meal frequency, home gardening practices, pulses production, delivery at health center, practice of income generating activity, food insecurity, and mobile phone usage had significant association with dietary diversity. Therefore, concerned bodies should design multidimensional livelihood and health service programs to alleviate inadequate dietary diversity.